Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1109/taslp.2021.3133216
|View full text |Cite
|
Sign up to set email alerts
|

Live Streaming Speech Recognition Using Deep Bidirectional LSTM Acoustic Models and Interpolated Language Models

Abstract: Although Long-Short Term Memory (LSTM) networks and deep Transformers are now extensively used in offline ASR, it is unclear how best offline systems can be adapted to work with them under the streaming setup. After gaining considerable experience on this regard in recent years, in this paper we show how an optimized, low-latency streaming decoder can be built in which bidirectional LSTM acoustic models, together with general interpolated language models, can be nicely integrated with minimal perfomance degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Amateur programmers and developers use question and answer websites like Stack Overflow for help during programming [12]. To assist Stack Overflow readers, researchers have proposed a range of proposals, including automatic tag suggestions and question templates for users asking questions [31], API abuse warnings [23], and API descriptions [28]. With the exception of preexisting synonymous tag pairs offered by Stack Overflow Beyer et al suggested a tool to provide synonymous tags for an input tag.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Amateur programmers and developers use question and answer websites like Stack Overflow for help during programming [12]. To assist Stack Overflow readers, researchers have proposed a range of proposals, including automatic tag suggestions and question templates for users asking questions [31], API abuse warnings [23], and API descriptions [28]. With the exception of preexisting synonymous tag pairs offered by Stack Overflow Beyer et al suggested a tool to provide synonymous tags for an input tag.…”
Section: Related Workmentioning
confidence: 99%
“…Example Check is a plugin for detecting API calls that are utilized incorrectly in stack overflow code snippets. It also shows how to utilise APIs correctly, including examples to help users learn how to use them properly [23]. It is proposed that StackDoc be used to enhance Stack Overflow with descriptions and examples of the Java APIs utilized in the inquiries [28].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, one related critical on-line recognition technology is ASR which has extensively applied the adaption of LSTM networks. An optimized, low-latency streaming decoder built with bidirectional LSTM acoustic models, together with general interpolated language models published recently in Jorge et al 22…”
Section: Related Workmentioning
confidence: 99%
“…FSN), that is typically applied under the off-line setting. Instead, we applied the Weighted Moving Average (WMA) technique, that uses the content of the current context window to update normalization statistics on-the-fly, weighted by previous context from past windows with an α parameter(Jorge, Giménez, Silvestre-Cerdà, et al 2022). Finally, as Transformer LMs have the inherent capacity of attending to potentially infinite word sequences, history is limited to a given maximum number of words, in order to meet the strict computational time constraints imposed by the streaming scenario.…”
mentioning
confidence: 99%